2019
DOI: 10.1155/2019/7541863
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Bath Temperature and Deposition Time on Topographical and Optical Properties of Nanoparticles ZnS Thin Films Synthesized by a Chemical Bath Deposition Method

Abstract: In this paper, zinc sulfide nanoparticle (ZnS-NP) thin films were deposited onto glass substrates by chemical bath deposition using zinc sulfate as the cation precursor and thiourea as the anionic precursor. Different bath temperatures (65, 70, 75, and 80°C) and different deposition times (20, 30, 40, and 50 min) were selected to study the performance of ZnS thin films. Topographical and optical characterizations of the films were studied using the atomic force microscope (AFM) and UV-Vis spectroscope. The bes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…On the other hand, we found that film thickness (1.4 to 1.7µm) increased with increasing temperature. The temperature effect on the film thickness has been reported by many researchers [43,44]. Figure 2 indicates the XRD patterns for the cobalt selenide thin films prepared under various bath temperatures.…”
Section: Imentioning
confidence: 73%
“…On the other hand, we found that film thickness (1.4 to 1.7µm) increased with increasing temperature. The temperature effect on the film thickness has been reported by many researchers [43,44]. Figure 2 indicates the XRD patterns for the cobalt selenide thin films prepared under various bath temperatures.…”
Section: Imentioning
confidence: 73%
“…Many researchers reported that more and more big particles appeared as the deposition time was increased. Further, they explain that the growth of particles (same deposition temperature) strongly depended onto longer deposition time [46][47][48][49][50].…”
Section: Advantages Of Silar Methods Limitations Of Other Deposition ...mentioning
confidence: 99%
“…For the deposition of ZnS thin films via CBD, some factors should be considered and controlled. These factors include Zn precursor, S precursor, complexing agent, pH of the mixture, bath temperature, and deposition time [30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%